Artificial Intelligence in Industry 4.0 and 5G Technology - Vasant, Pandian; Munapo, Elias; Thomas, J. Joshua 1973-; Weber, Gerhard-Wilhelm 1960- (John Wiley & Sons, Inc., 2022)
Artificial Intelligence in Industry 4.0 and 5G Technology Explores innovative and value-added solutions for application problems in the commercial, business, and industry sectors As the pace of Artificial Intelligence (AI) technology innovation continues to accelerate, identifying the appropriate AI capabilities to embed in key decision processes has never been more critical to establishing competitive advantage. New and emerging analytics tools and technologies can be configured to optimize business value, change how an organization gains insights, and significantly improve the decision-making process across the enterprise. Artificial Intelligence in Industry 4.0 and 5G Technology helps readers solve real-world technological engineering optimization problems using evolutionary and swarm intelligence, mathematical programming, multi-objective optimization, and other cutting-edge intelligent optimization methods.
Keywords: Artificial intelligence / Industrial applications; Industry 4.0; 5G mobile communication systems; Artificial intelligence - Industrial applications